2011
DOI: 10.1042/bse0510047
|View full text |Cite
|
Sign up to set email alerts
|

African trypanosomes: the genome and adaptations for immune evasion

Abstract: The African trypanosome Trypanosoma brucei is a flagellated unicellular parasite transmitted by tsetse flies that causes African sleeping sickness in sub-Saharan Africa. Trypanosomes are highly adapted for life in the hostile environment of the mammalian bloodstream, and have various adaptations to their cell biology that facilitate immune evasion. These include a specialized morphology, with most nutrient uptake occurring in the privileged location of the flagellar pocket. In addition, trypanosomes show extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…In effect, Rudenko concluded that the extensive potential for VSG switching gives T. brucei gambiense a modifiable patchwork surface, with the H1 histone reflecting a checkpoint mechanism to T. brucei gambiense chronicity [1,2]. Increased research into antigen switching in T. brucei gambiense may assist in understanding the mechanisms underlying other pathogen antigen switch strategies and hopefully stimulate therapeutic design to overcome this strategy of host immune evasion.…”
Section: Denuding Trypanosoma Bruceimentioning
confidence: 99%
See 2 more Smart Citations
“…In effect, Rudenko concluded that the extensive potential for VSG switching gives T. brucei gambiense a modifiable patchwork surface, with the H1 histone reflecting a checkpoint mechanism to T. brucei gambiense chronicity [1,2]. Increased research into antigen switching in T. brucei gambiense may assist in understanding the mechanisms underlying other pathogen antigen switch strategies and hopefully stimulate therapeutic design to overcome this strategy of host immune evasion.…”
Section: Denuding Trypanosoma Bruceimentioning
confidence: 99%
“…In collaboration, Rudenko's group determined that H1 knockdown effected a more open T. brucei gambiense chromatin structure, leading to increased VSG switching, with normally silent VSG expression sites particularly sensitive [1,2].…”
Section: Denuding Trypanosoma Bruceimentioning
confidence: 99%
See 1 more Smart Citation
“…Each has a glycoprotein coat composed of a stage-specific major surface glycoprotein: procyclins in the PCF stage (7) and variant surface glycoproteins (VSGs) in the BSF stage (8). Both VSGs and procyclins play pivotal roles in pathogenesis, VSG as the lynchpin of antigenic variation in the mammalian bloodstream (9) and procyclin as a critical component facilitating colonization in the tsetse midgut (10). In addition, there are many less abundant surface glycoproteins including invariant surface antigens, transferrin receptor, and other nutrient transporters that are critical to the success of these important human pathogens (11).…”
mentioning
confidence: 99%
“…Both are glycosylphosphatidylinositol (GPI) anchored and N-glycosylated, and there are distinct stage-specific variations for each class of glycomodification (12). In PCF cells only oligomannose N-glycans (Man 9 GlcNAc 2 ) are transferred to nascent glycoproteins, and these are typically trimmed to small triantennary (Man 5 GlcNAc 2 ) structures (13,14); subsequent extension by addition of other hexose units in the Golgi apparatus has not been found. In addition to this kind of N-glycosylation, BSF cells are also capable of transferring abbreviated biantennary paucimannose structures (Man 5 GlcNAc 2 ), and these can be trimmed and extended in the Golgi apparatus by addition of N-acetyllactosamine (LacNAc, Gal␤1-4GlcNAc) units (15,16).…”
mentioning
confidence: 99%